Perubahan Fonologi Kata Serapan Bahasa Arab dalam Bahasa Indonesia, Studi Kasus Kosakata Agama Islam pada KBBI Online - Muhammad Nauval Shah; Zaqiatul Mardiah (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2023)
This article is a phonological change research of Arabic loanwords in Indonesian from KBBI Online dictionary within knowledge realm of Islamic religion according to phonological changes study by Masnur Muslich. There are two problems that will be examined, that is how the phonological changes occured on the Arabic loanwords in Islamic context on KBBI, and to analyze whether native Arabic speaker can understand these loanwords when pronounced. Research materials for article are Arabic loanwords within Islamic context from KBBI Online that will be taken randomly. Research method applied to answer the problem is qualitative method, while data collection is done using document study technique. The research has shown that loanwords pronunciation changed by anaptyxis, neutralization and vocal modification. Loanwords sound usually changed by neutralization to represent the sound of Arabic word that doesn’t have any sound representation in Indonesian and vocal modification to shorten the Arabic vocal pronunciation so native Arabic speakers won’t understand sound of these words.Keywords– Arabic, Indonesian, Loanwords, Phonology.